Application of a Colored Multiexposure High Dynamic Range Technique to Radiographic Imaging: An Experimental Trial to Show Feasibility. Issue 4 (July 2016) - Eppenberger, Patrick; Marcon, Magda; Ho, Michael; Del Grande, Filippo; Frauenfelder, Thomas; Andreisek, Gustav
Abstract : Purpose: The aim of this study was to evaluate the feasibility of applying the high dynamic range (HDR) technique to radiographic imaging to expand the dynamic range of conventional radiographic images using a colored multiexposure approach. Material and Methods: An appropriate study object was repeatedly imaged using a range of different imaging parameters using a standard clinical x-ray unit. An underexposed image (acquired at 80 keV), an intermediate exposed image (110 keV), and an overexposed image (140 keV) were chosen and combined to a 32-bit colored HDR image. To display the resulting HDR image on a regular color display with typically 8 bits per channel, the Reinhard tone mapping algorithm was applied. The source images and the resulting HDR image were qualitatively evaluated by 5 independent radiologists with regard to the visibility of the different anatomic structures using a Likert scale (1, not visible, to 5, excellent visibility). Data were presented descriptively. Results: High dynamic range postprocessing was possible without malalignment or image distortion. Application of the Reinhardt algorithm did not cause visible artifacts. Overall, postprocessing time was 7 minutes 10 seconds for the whole process. Visibility of anatomic structure was rated between 1 and 5, depending on the anatomic structure of interest. Most authors rated the HDR image best before individual source images. Conclusions: This experimental trial showed the feasibility of applying the HDR technique to radiographic imaging to expand the dynamic range of conventional radiographic images using a colored multiexposure approach.